2019
DOI: 10.1093/jac/dkz150
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of linezolid-resistance-associated mutations in Mycobacterium tuberculosis through WGS

Abstract: Objectives Linezolid is becoming an important antibiotic for treating MDR/XDR TB, but the mutations conferring resistance to linezolid remain inadequately characterized. Herein, we investigated the linezolid-resistance-associated mutations on a whole-genome scale through parallel selections of resistant isolates in vitro. Methods Ten parallel Mycobacterium tuberculosis H37Rv cultures were subjected to spontaneous mutant selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 19 publications
0
9
1
Order By: Relevance
“…Before LZD is used on a global scale, understanding mechanisms of LZD resistance is essential in order to guide formulation of optimal drug combinations with LZD. So far, mutations in ribosomal genes 23S rRNA (encoding ribosomal RNA, rrl ) and rplC (encoding the L3 protein) have been identified as the predominant molecular mechanisms associated with LZD resistance in MTB ( Beckert et al, 2012 ; Zhang et al, 2014 , 2016 ; Pi et al, 2019 ). Nevertheless, due to limited use of this costly drug, MTB resistance to LZD is still a rare phenomenon in clinical settings, with most LZD-resistant mutants identified only after in vitro selection ( Zimenkov et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Before LZD is used on a global scale, understanding mechanisms of LZD resistance is essential in order to guide formulation of optimal drug combinations with LZD. So far, mutations in ribosomal genes 23S rRNA (encoding ribosomal RNA, rrl ) and rplC (encoding the L3 protein) have been identified as the predominant molecular mechanisms associated with LZD resistance in MTB ( Beckert et al, 2012 ; Zhang et al, 2014 , 2016 ; Pi et al, 2019 ). Nevertheless, due to limited use of this costly drug, MTB resistance to LZD is still a rare phenomenon in clinical settings, with most LZD-resistant mutants identified only after in vitro selection ( Zimenkov et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the Mycobacterium tuberculosis complex (MTBC), at the species scale, thousands of single-nucleotide polymorphisms (SNPs) have been identified in numerous virulence genes [16]. In addition, multiple studies have also shown the importance of AA changes in the evolution of other molecular determinants of the MTBC, such as in RskA [17] and PhoR [18], and during the emergence of antibiotic resistant mutants [19,20]. These point mutations have also helped establish the evolutionary relationships between several lineages and were even suggested to be useful as broad phylogenetic markers [15,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, such strains remain scarce. For LNZ, only one SNV in rplC determining the well-known substitution C154R was observed in a resistant strain (Pi et al, 2019), and we did not find NSUV in the other LNZ-R strains tested. For BDQ, it has been previously reported that mutations in Rv0678 are mainly responsible for low-level resistance to BDQ rather than high-level resistance (Nguyen et al, 2018).…”
Section: Nsuvscontrasting
confidence: 60%
“…With 79/84 Deeplex Myc-TB results in accordance with DST, the concordance value was high for linezolid (LNZ) (94%), but we noticed three Deeplex Myc-TB failures and two LNZ-R strains with no detectable mutations in rrl or in rplC (Table 4). We observed no uncharacterized mutations, and the only LNZ-R strain was due to the well-known substitution C154R (data not shown) (Pi et al, 2019).…”
Section: Performance Of Genelead/deeplex Myc-tb To Detect Antitb Drug Resistance In Mtbcmentioning
confidence: 73%